Internalisasi Nilai Kejujuran pada Pembelajaran PPKn di SMP Negeri 1 Jongkat - Dilla Tri Aprilia; Bistari Bistari; Shilmy Purnama; Sulistyarini Sulistyarini; Achmadi Achmadi (Journal on Education, 2024)
Schools are the leading institutions in developing character education. Schools have a moral responsibility to educate children to be intelligent and have positive character as their parents hope. However, it cannot be denied that in reality, educational practices in Indonesia are still not optimal. This research aims to determine the internalization of the value of honesty in class VIIID students at SMPN 1 Jongkat. This research method uses descriptive qualitative methods. Data collection techniques in this research used observation, questionnaires, interviews and documentation techniques. The results of this research are that the honesty score for class VIIID students is considered successful with a percentage of positive statements of 72.2% and negative statements of 83.7%. From these results it can be seen that students already have the value of honesty which can be applied both within the school environment and outside the school environment. The conclusion of this research is that a form of internalization of the value of honesty towards students can be seen in learning in the classroom through teaching and learning activities.